2010
DOI: 10.1017/s0022109010000633
|View full text |Cite
|
Sign up to set email alerts
|

Has the Propensity to Pay Out Declined?

Abstract: Recent studies document both a significant decline in firms’ propensity to pay dividends and a significant increase in firms’ propensity to repurchase shares and issue equity over the past 30 years. In this paper we test whether firms’ net cash disbursements to equity holders have declined in a pattern similar to firms’ propensity to pay dividends. Contrary to the evidence using dividends, we find no evidence that the conditional propensity to distribute net cash to equity holders has declined over the past 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…First, following Boudoukh, Michaely, Richardson, and Roberts (), we calculate total payout as dividends (# dvc) plus repurchases (total expenditure on the purchases of common and preferred stock (# prstkc) plus any reduction in the value of the net number of preferred stock outstanding (# pstkrv)). Following Grullon, Paye, Underwood, and Weston () and Banyi, Dyl, and Kahle (), we define the determinants of total payout as the relative market capitalization (the percentile in which the firm falls on the distribution of equity market values for NYSE firms in year t ), book‐to‐market ratio (# ceq/(# prcc_f × # csho)), return on assets (# ib/# at), sales growth (# sale/lagged # sale − 1), the logarithm of number of years since IPO, the logarithm of stock return volatility, retained earnings (# re/# at), stock options outstanding (# optosey/# csho), leverage ((# dltt + # dlc)/# at), the logarithm of total assets (# at), free cash flows ((# oibdp − (# txt − # txditc + lagged # txditc) − # tie − # dvp − # dvc)/(# prcc_f × # csho)), and stock returns. To come up with a prediction of total payout, we use the entire COMPUSTAT population from 2000 to 2008 to estimate a Tobit regression of total payouts on the above determinants, inclusive of year and industry fixed effects.…”
Section: Methodsmentioning
confidence: 99%
“…First, following Boudoukh, Michaely, Richardson, and Roberts (), we calculate total payout as dividends (# dvc) plus repurchases (total expenditure on the purchases of common and preferred stock (# prstkc) plus any reduction in the value of the net number of preferred stock outstanding (# pstkrv)). Following Grullon, Paye, Underwood, and Weston () and Banyi, Dyl, and Kahle (), we define the determinants of total payout as the relative market capitalization (the percentile in which the firm falls on the distribution of equity market values for NYSE firms in year t ), book‐to‐market ratio (# ceq/(# prcc_f × # csho)), return on assets (# ib/# at), sales growth (# sale/lagged # sale − 1), the logarithm of number of years since IPO, the logarithm of stock return volatility, retained earnings (# re/# at), stock options outstanding (# optosey/# csho), leverage ((# dltt + # dlc)/# at), the logarithm of total assets (# at), free cash flows ((# oibdp − (# txt − # txditc + lagged # txditc) − # tie − # dvp − # dvc)/(# prcc_f × # csho)), and stock returns. To come up with a prediction of total payout, we use the entire COMPUSTAT population from 2000 to 2008 to estimate a Tobit regression of total payouts on the above determinants, inclusive of year and industry fixed effects.…”
Section: Methodsmentioning
confidence: 99%
“…I follow the sample selection criteria used by recent studies (Grullon et al., ) in the related literature. My sample includes US firms with available dividend data and accounting information from Compustat and stock price information from CRSP in the period from 1990 to 2010.…”
Section: Data Sample Selection and Summary Statisticsmentioning
confidence: 99%
“…Although they note that agency models predict that lower agency costs will result in higher total payout over time, when the payout occurs can depend on the firm's investment opportunities and life cycle. Hence, we include in our multivariate regression analysis of payout the proxies for institutional monitoring described above, as well as 12 other firm characteristics possibly related to payout policy (Grinstein and Michaely ; Grullon et al, ): Size is the natural log of sales reported by Compustat, measured in millions of dollars. Market to Book is the market value of common equity reported by Compustat divided by the book value of common equity. Excess Return is the annual stock return adjusted by the CRSP value‐weighted annual return. Beta is calculated by regressing daily stock returns for the year onto the CRSP value‐weighted daily returns. Age is the number of months since the firm's first return is reported in CRSP. Market Return on Assets is operating income before depreciation divided by the firm's total market value Sales Growth is calculated as the percentage change in sales revenue reported in Compustat over the previous year. Stock Volatility is calculated from CRSP as the firm's standard deviation of daily stock returns for the year. Retained Earnings is retained earnings reported in Compustat scaled by market value of common equity. Sales Diversity is a Herfindahl index of sales diversification within a firm's operating segments; segments are categorized by four‐digit SIC codes. Change in Sales Diversity is the difference between Sales Diversity for the current and prior fiscal year Dual Class Dummy is a binary variable indicating a firm has two classes of common stock, one of which has inferior voting rights. …”
Section: Methodology and Quantitative Resultsmentioning
confidence: 99%
“…Though Table does not provide variable averages by year, we nevertheless note that total payout does not exhibit dividends' well‐documented time trend. As Grinstein and Michaely () and Grullon et al () show, dividend payout has steadily declined since the 1980s while repurchases have steadily grown. Therefore, although dividends average 0.91% of assets in the first third of the sample and repurchases average only 0.79% (total payout: 1.70%), in the final third of the sample dividends average 0.58% of assets and repurchases 1.31% (total payout: 1.89%).…”
Section: Data Set Description and Measures Of Monitoringmentioning
confidence: 97%